x(x+3)=x+3

Simple and best practice solution for x(x+3)=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+3)=x+3 equation:


Simplifying
x(x + 3) = x + 3

Reorder the terms:
x(3 + x) = x + 3
(3 * x + x * x) = x + 3
(3x + x2) = x + 3

Reorder the terms:
3x + x2 = 3 + x

Solving
3x + x2 = 3 + x

Solving for variable 'x'.

Reorder the terms:
-3 + 3x + -1x + x2 = 3 + x + -3 + -1x

Combine like terms: 3x + -1x = 2x
-3 + 2x + x2 = 3 + x + -3 + -1x

Reorder the terms:
-3 + 2x + x2 = 3 + -3 + x + -1x

Combine like terms: 3 + -3 = 0
-3 + 2x + x2 = 0 + x + -1x
-3 + 2x + x2 = x + -1x

Combine like terms: x + -1x = 0
-3 + 2x + x2 = 0

Factor a trinomial.
(-3 + -1x)(1 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-3, 1}

See similar equations:

| n*7-9=33 | | -x^2+57x=540 | | 5x=3(4+1) | | 13x-12=2x+142 | | 5y^2-8y=-2 | | -x^2=54 | | lgx=5 | | (x*x)(x*x)(x*x)= | | X+2.1=3x-0.6 | | 1000*t=8.4594 | | 4.4*q=40.04 | | (8*8)(8*8)= | | 5w-2n=w | | 14-8n=12 | | 5-3n=-10 | | 158*2.4= | | 20-2n=6 | | 0.916*8.2= | | 4n+4=16n | | 10n=20-10n | | 3n=n+63 | | a*a*a*a*a= | | 4x+6.2=0.4-x | | 70.5-70.36= | | 3x+42=6-6 | | 3(x+4)-8=7 | | 11n=2n+27 | | -5x+13x=18 | | 10n-8=102 | | 3n-7=21 | | 6*z+5=15 | | 12x=-2x+10x |

Equations solver categories